The application of market power theory as a value driver for information technology investment decisions : a study of six Chilean banks : a thesis submitted in partial fulfilment of the requirement for the degree of Doctor of Business Administration /: a study of six Chilean banks : a thesis submitted in partial fulfilment of the requirement for the degree of Doctor of Business Administration. (2013) - Griffiths, Paul D. R
No abstract available